(untitled) (Journal of the College of Basic Education, 2023)
The two most influential forces in the life of Tennessee Williams were his writing and his sister Rose. By no accident, many of his male characters are artists, and many of his female characters, like Rose, suffer from some condition that makes them alienated from the world and emotionally unprepared to dealwith its hardship. This study is an examination of the relationship between William’s male artist and fragile female characters in each of the plays in which the two figures are found. It reveals that through these two characters and the progress of their relationship, Williams expressed the inner emotional turmoil of his own life. By the end of his work, Williams created an unsustainable bond between his writer and fragile female, allowing them to live, flourish, and care for one another in a way that he and Rose never could.